IL-1β Impaired Diabetic Wound Healing by Regulating MMP-2 and MMP-9 through the p38 Pathway - Jiezhi Dai; Junjie Shen; Yimin Chai; Hua Chen (Hindawi Limited, 2021)
Diabetes mellitus is one of the most prominent metabolic disorders in the world, and insulin resistance in diabetic patients leads to several complications including increased inflammation and delayed wound healing. Fibroblast migration and reepithelialization play a significant role in wound healing. In this study, we explored the effects of IL-1β signaling on proliferation and migration of human fibroblasts from diabetic wound tissues. We observed elevated levels of IL-1β in samples from diabetic patients when compared to normal wound tissues. At high concentrations, IL-1β inhibited cell proliferation and migration in ex vivo fibroblast cultures. Moreover, expression of matrix metalloproteinases (MMPs) was upregulated, and tissue inhibitor of metalloproteinases (TIMPs) was downregulated in diabetic wound tissues and cells. These effects were regulated by levels of IL-1β. Furthermore, IL-1β induced p38 phosphorylation thereby activating the p38 MAPK pathway that in turn regulated the expression of MMPs and TIMPs. Together, our study identifies a novel mechanism behind delayed wound closure in diabetes mellitus that involves IL-1β-dependent regulation of cell proliferation and migration.